Rotavirus Viroplasm Proteins Interact with the Cellular SUMOylation System: Implications for Viroplasm-Like Structure Formation - Campagna, Michela (American Society for Microbiology, 2013)
Posttranslational modification by SUMO provides functional flexibility to target proteins. Viruses interact extensively with the cellular SUMO modification system in order to improve their replication, and there are numerous examples of viral proteins that are SUMOylated. However, thus far the relevance of SUMOylation for rotavirus replication remains unexplored. In this study, we report that SUMOylation positively regulates rotavirus replication and viral protein production. We show that SUMO can be covalently conjugated to the viroplasm proteins VP1, VP2, NSP2, VP6, and NSP5. In addition, VP1, VP2, and NSP2 can also interact with SUMO in a noncovalent manner. We observed that an NSP5 SUMOylation mutant protein retains most of its activities, such as its interaction with VP1 and NSP2, the formation of viroplasm-like structures after the coexpression with NSP2, and the ability to complement in trans the lack of NSP5 in infected cells. However, this mutant is characterized by a high degree of phosphorylation and is impaired in the formation of viroplasm-like structures when coexpressed with VP2. These results reveal for the first time a positive role for SUMO modification in rotavirus replication, describe the SUMOylation of several viroplasm resident rotavirus proteins, and demonstrate a requirement for NSP5 SUMOylation in the production of viroplasm-like structures.